2008
DOI: 10.1002/hlca.200890207
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oxygenated Triterpenoids from the Marine Red Alga Laurencia mariannensis (Rhodomelaceae)

Abstract: Two new and one known squalenoid-derived triterpenoids, namely, laurenmariannol (1) and (21a)-21-hydroxythyrsiferol (2), and the known thyrsiferol (3) were isolated and identified from the marine red alga Laurencia mariannensis, which was collected off the coast of Hainan and Weizhou Islands of China. The structures of these compounds were established by means of spectroscopic analyses, as well as by comparison with literature data. Compounds 1 and 2 displayed significant cytotoxic activity against P-388 tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…It should be noted that 21α-hydroxythyrsiferol (367) and laurenmariannol (368) were reported as new compounds from L. mariannensis in 2008. 243 However, the spectroscopic data of these two compounds were very similar to those of aplysiols A and B, which were isolated from the sea hare Aplysia dactylomela in 2007. 244 Sea hare are known to feed upon Laurencia species, and it thus seems likely that the true origin of these compounds is dietary algae.…”
Section: Halogenated Triterpenes/polyethersmentioning
confidence: 69%
See 1 more Smart Citation
“…It should be noted that 21α-hydroxythyrsiferol (367) and laurenmariannol (368) were reported as new compounds from L. mariannensis in 2008. 243 However, the spectroscopic data of these two compounds were very similar to those of aplysiols A and B, which were isolated from the sea hare Aplysia dactylomela in 2007. 244 Sea hare are known to feed upon Laurencia species, and it thus seems likely that the true origin of these compounds is dietary algae.…”
Section: Halogenated Triterpenes/polyethersmentioning
confidence: 69%
“…230 Of these, thyrsiferyl 23-acetate (349) displayed the most potent activity against P-388 cells, with an ED 50 (367) and laurenmariannol (368) also showed cytotoxicity toward P-388 with IC 50 values of 6.6 and 0.60 μg/mL, respectively. 243 Further examination revealed that thyrsiferyl 23-acetate (349) induced rapid cell death in various leukemic T-and B-cell lines, and that the cell death follows a typical apoptotic process. 501 Thyrsiferol (347) inhibited hypoxia-inducible factor-1 (HIF-1) activation in T47D human breast tumor cells.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…A detailed NMR comparison with those reported for phytyl acetate revealed that 4 differed from phytyl acetate mainly at C(2) and C(3) [25]. The olefinic 13 (2)) of phytyl acetate [25] was replaced by an epoxy signal at d(H) 2.98 (dd, J ¼ 6.9, 4.3 Hz, HÀC(2)) in 4. So, compound 4 was deduced to be a 2,3-epoxy derivative of phytyl acetate.…”
mentioning
confidence: 81%
“…Chemical investigation of L. nidifica for secondary metabolites started from 1974 [1] and the majority of these metabolites are halogenated sesquiterpenes and C 15 -acetogenins [2,3], many of which possess antimicrobial and antiviral activities [2,4]. In our continuing investigation on halogenated bioactive natural products from Laurencia species [5][6][7][8][9][10][11][12][13][14], we casually collected the species L. nidifica from Sanya coast of Hainan Province. Chemical examination of this species resulted in the isolation and identification of a new brominated C 15 -acetogenin, namely, laurenidificin (1) (Fig.…”
mentioning
confidence: 99%